Opportunities and Adjustment Strategies of College Students During Adversities for Improved Academic Performance - Zhu, Yuzhi (Pacific International Journal, 2024)
This study explored opportunities and adjustment strategies of Chinese graduate students in blended learning. A survey among 102 students using validated questionnaires found overall low opportunities except moderate challenges managing home environments. Students frequently employed active coping like positive thinking and problem analysis, rarely passive strategies. No demographic differences existed. More opportunities correlated with poorer academic performance, mitigated by greater adjustment strategy use. Recommendations include maximizing interactive activities, strengthening time management, increasing teacher consultations, and building peer support. The study provides insights into facilitating personalized, inclusive, resilient blended learning through enhancing spaces, progress monitoring, integrating support systems. Further research can uncover nuanced perspectives to inform evidence-based improvements in policies, pedagogies, and environments for empowering self-directed, motivated learning.